The Differences Of Parents Patterns Permisive and Authorities Towards Free Sex Events: Perbedaan Pola Asuh Orang Tua Permisif dan Otoriter Terhadap Kejadian Seks Bebas - Evin Noviana Sari (Poltekkes Kemenkes Medan, 2020)
Background: Permissive parenting is a parenting style in which parents are not involved in their child's life, especially lack of self-control. Usually permissive parenting does not guide children to social behavior patterns and does not use punishment, while authoritarian parenting is one in which parents are central in speech. The purpose of this study was to determine the differences in permissive and oratory parenting patterns on the incidence of free sex in adolescents.Methods: Sampling using a minimum sample, when the study was conducted on June 21, 2020 at SMA Unggul Dharmasraya Regency. The design in this study is an independent sample T Test, the sample taken in this study was 20 people divided into two groups, namely the permissive parenting group and authoritarian parenting. In the bivariate analysis, the normality test uses the Shapiro Wilk, if the data is normally distributed, the bivariate test using the independent test uses the independent T test sample, but the data is not normally distributed, using the Mann Whitney U Test bivariate test using theprogram SPSS.Results of the study / discussion: From the results of the analysis of permissive parenting styles, 8 (80%) respondents were cared for with permissive parenting and authoritarian parenting 6 (60%) of respondents who were cared for by authoritarian parenting, to the incidence of free sex12 (60%) respondents who occur free sex, and the results of differences in permissive parenting and authoritarian parenting on the incidence of free sex, which shows a sig or p-value of 0.144> 0.05, meaning that there is no difference in permissive parenting and authoritarian parenting on the incidence of free sex. Conclusion: So the role of parents for children is to guide and teach children on good things, in accordance with the values ??and norms that apply in society